Effects of grain boundary structure and shape of the solid–liquid interface on the growth direction of the grain boundaries in multicrystalline silicon. Issue 10 (17th February 2022) - Fukuda, Yusuke; Kutsukake, Kentaro; Kojima, Takuto; Usami, Noritaka
Abstract : The unique samples fabricated using seed crystals with artificial grain boundaries (GBs) allowed a systematic investigation of the effect of the macroscopic GB structure (orientation, asymmetric angle, Σ values) on the GB growth direction. Abstract : We report on the effects of grain boundary (GB) structure on the growth direction of the GBs by utilizing silicon ingots with artificially designed asymmetric tilt GBs. The ingots were grown by directional solidification using the seed crystal formed by combining multiple <110>-oriented or <100>-oriented single crystalline silicon crystals with controlled GB planes, which could offer a unique opportunity for systematic investigation of the influences of misorientation and asymmetry. We found that GBs in <110>-oriented ingots grow along the seed-oriented direction, while those in <100>-oriented ingots grow away from the seed-oriented direction accompanied by the introduction of the twist component. These phenomena are explained in terms of energy minimization, assuming a linear increase of the GB energy as a function of the deviation angle and its dependence on the orientation. Specifically, we revealed that GBs with shallow energy grooves such as <100> tilt GBs are more likely to grow away from the seed-oriented direction than energetically stable GBs.